Analysis of the production conditions of geopolymer matrices from natural pozzolana and fired clay brick wastes - Silva, G.; Castañeda, D.; Kim, S.; Castañeda, A.; Bertolotti, B.; Ortega-San-Martín, L.; Nakamatsu, J.; Aguilar, R. (Elsevier, 2019)
The improvement of the mechanical properties of geopolymer matrices relies on the characteristics of the source materials as well as in proper optimization of the alkaline activating solution and curing conditions during geopolimerization. This study presents the optimization analyses carried out to determine the proper production conditions of Fired Clay Brick (FCB) and Natural Pozzolana (NP)-based geopolymers. The results indicate that high compressive strengths of up to 37 MPa and 26 MPa can be obtained for FCB and NP-based geopolymers, respectively when the proper production conditions are employed. The optimum alkaline solution for FCB consisted of Ms = 0.60, Na2O content of 8%, water/binder ratio = 0.27 with oven curing conditions between 65 and 80 °C for 7 days. On the other hand, NP-based geopolymers with the highest mechanical properties were obtained with an alkaline solution composed of a Ms = 1.08, 8% Na2O content and 0.52 of water/binder ratio cured in an oven at 65 °C for 7 days. The methodology for the optimization of production conditions of geopolymer matrices validated in this study demonstrated to provide consistent results and, therefore, could be applied for the analysis of the production process of geopolymers based on other aluminosilicate sources.
Keywords: Geopolymerization; https://purl.org/pe-repo/ocde/ford#2.04.00